Virtual psychological consultation: support for the current population - Rodríguez Vílchez, Edgar (2013)
With the passing of years, the mental health has taken greater importance, now there are institutions that promote activities or events in favor for the mental well-being of people. Although there are alternatives since several years ago, such as counseling and guidance, this type of care has served to connect with technology, becoming virtual psychological clinics, for people who can´t attend a consultation “face to face”. In our country there are these kinds of support that is supported by “Universia”, and attended by a team of Unife´s psychologists, from about ten years ago, where people continue attending to communicate their consultation motive and waiting for a response that lead and guide to find some type of alternative to improve their difficulty. In the past three years (2010, 2011 and 2012), among the most common consultation motives there are: addictions (compulsive gambling and consumption of psychoactive substances), family problems, mood disorders and vocational training.